Competitive sports, the Coronavirus disease 2019 pandemic, and Big Ten athletics - Rink. L. D.; Daniels, C. J.; Boersma, D.; Borchers, J.; Busch, J.; Kovan, J.; Kratochvil, C.; Rifat, S.; Rosenthal, G.; Chung, E. H. (Circulation, 2020)
In February 2020, a number of institutions within the Big Ten began discussing the impact of coronavirus disease 2019 (COVID-19) on sports. On March 7, the Big Ten Task Force for Emerging Infectious Diseases was formed to provide council and sound medical advice to ensure the health, safety, and wellness of the Big Ten`s students, staff and fans. On March 11, 2020, the National Basketball Association postponed its season after the first player tested positive for COVID-19 infection. The next day, college basketball tournament games were canceled. The issues at hand were clear: the multi-organ adverse effects (including cardiac), high rate of transmission, and overall uncertainty about short and long term effects of the coronavirus raised serious concerns about player safety as well as sports` role in propagation of the virus across the broader community. In this Perspective, the Big Ten Cardiac Registry Steering Committee reflects on the last several months through a series of questions. Our committee is made up of conference administrators and physicians in sports medicine, infectious disease, and cardiology. We look ahead to opportunities to return to play and contribute to public health. These reflections may be valuable to other organizations also struggling with how to best balance decisions for their members in the setting of imperfect information.